2011
DOI: 10.21236/ada548948
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Optical Response Properties of MEH-PPV Semiconductor Polymer Schottky Diodes

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden, to Department of Defense, Washington Headquarters Services, Directorate for Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…6,7 The MEH-PPV acts as an electron donor (p-type semiconducting polymer) with a relatively low conductivity due to its low hole and electron mobilities when compared to inorganic semiconductor materials. 8,9 Soluble organic semiconductors for OLEDs have received important attention since they offer a potential for the production by solution processing techniques such as spincoating, ink-jet printing or drop casting. 10,11 Within this, the conjugated organic polymers have been generally considered as a suitable material for these techniques because of their good lm forming capacity.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The MEH-PPV acts as an electron donor (p-type semiconducting polymer) with a relatively low conductivity due to its low hole and electron mobilities when compared to inorganic semiconductor materials. 8,9 Soluble organic semiconductors for OLEDs have received important attention since they offer a potential for the production by solution processing techniques such as spincoating, ink-jet printing or drop casting. 10,11 Within this, the conjugated organic polymers have been generally considered as a suitable material for these techniques because of their good lm forming capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we demonstrated MEH-PPV:VOPCPhO [ 11 ] and MEH-PPV:Alq 3 [ 12 ] binary blend-based photodetectors. MEH-PPV exhibits fairly good hole mobility and environmental stability [ 21 ]. However, the photosensitivities and the photo to the dark current ratios of both binary blends-based OPDs were relatively lower.…”
Section: Introductionmentioning
confidence: 99%